The Customary and Existing Order: Reconsidering the Role of Yamm in the Baal Myth: LXXSA - Putrawan, Bobby Kurnia; Noya, Ludwig Beethoven Jones; Santoso, Agus; Iswahyudi (Journal for Semitics, 2023)
The conflict between Baal and Yamm in the Baal Cycle’s opening is notably considered a challenging scene to understand. This paper sees Yamm’s role as representing the customary and existing order rather than chaos or disorder. Such a function is revealed through Baal’s double paternity in the cycle. Instead of justifying one of the possibilities to read the conflict, this concept reconciles all possibilities in an alternative reading. Under the idea of Yamm as the customary and existing order, and Baal as the one who is attempting to disrupt the order, one can read the conflict politically, domestically, and naturally. However, as Baal’s propaganda, the defeated Yamm had to be portrayed as the opposite of order, namely chaos. The customary order has been broken and depicted as chaos for a political purpose: to promote the new order.